The Relationship between Subnormal Peak-Stimulated Growth Hormone Levels and Auxological Characteristics in Obese Children - Barrett, Jefferson; Maranda, Louise; Nwosu, Benjamin U. (Frontiers in Endocrinology, 2014)
Context: The hypothesis that obese children are overdiagnosed with growth hormone deficiency (GHD) has not been adequately investigated in the context of adiposity-related differences in auxology. Aim: To investigate the differences in auxological parameters between short, prepubertal, obese children and normal-weight peers who underwent growth hormone stimulation testing (GHST). Hypothesis: Overweight/obese children with GHD (peak GH< 10 µg/L) will have higher values for growth velocity (GV) standard deviation score (SDS), bone age minus chronological age (BA-CA), and child height SDS minus midparental height (MPTH) SDS when compared to normal-weight GHD peers. Subjects and Methods: A retrospective review of anthropometric and provocative GHST data of 67 prepubertal, GH-naïve children of age 10.21± 2.56 years (male n=45, age 10.8±2.60 years; female n=22, age 8.94±2.10). Inclusion criteria: GHST using arginine and clonidine. Exclusion criteria: hypopituitarism, abnormal pituitary MRI scan, syndromic obesity or syndromic short stature. Data were expressed as mean ± SD. Results: The overweight/obese children with peak GH of < 10 µg/L had significantly lower value for ln peak GH (1.45 ± 0.09 vs. 1.83 ± 0.35, p=0.022), but similar values for GV SDS, IGF-I, IGFBP-3, bone age, BA-CA, MPTH, and child height SDS minus MPTH SDS compared to normal-weight peers with GHD. After adjusting for covariates, the overweight/obese children (BMI≥85th percentile) were >7 times more likely than normal-weight subjects (BMI< 85th percentile) to have a peak GH of < 10 µg/L, and 23 times more likely to have a peak GH of < 7 µg/L (OR=23.3, p=0.021). There was a significant inverse relationships between BMI SDS and the natural log (ln) of peak GH (β=-0.40, r2=0.26, p=0.001), but not for BMI SDS vs. GV SDS, ln peak GH vs.BA, or ln peak GH vs. GV SDS. Conclusion: Subnormal peak GH levels in obese prepubertal children are not associated with unique pre-GHST auxological characteristics.